Union organisation and effectiveness: an empirical study on In-House Union in Malaysia. - Suhaila Mohamed; Faridahwati Mohd Shamsudin; Husna Johari (Universiti Kebangsaan Malaysia, 2010)
This research note attempts to present findings from a study that examined the relationship between the way an inhouse union organises itself and its delivery effectiveness. Data were gathered through a survey of union members of an in-house union of a manufacturing company in Kedah, Malaysia (n = 415) and analysed using correlation and multiple regression tests. The results suggest that, firstly, union organisation was significantly correlated with union effectiveness. Secondly, there were significant relationships between two of the four dimensions of union organisation (namely, communications within union, and union understanding of employer’s business) and union effectiveness. Finally, communication within union was the most important predictor of union effectiveness. The implications of the study on practice and theory are discussed.